2019
DOI: 10.3389/fmars.2019.00267
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Concentrations, Stocks, and Isotopic Compositions in Red Sea Seagrass and Mangrove Sediments

Abstract: Coastal vegetated ecosystems are intense global carbon (C) sinks; however, seagrasses and mangroves in the Central Red Sea are depleted in organic C (C org ). Here, we tested whether C org depletion prevails along the Red Sea, or if sediment C org and nitrogen (N) stocks reflect the latitudinal productivity gradient of the Red Sea. We assessed C org and N concentrations, stocks, isotopic compositions (δ 13 C and δ 15 N), and the potential contribution of primary producers to the organic matter accumulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…N limitation, thus, is reflected in low mangrove canopy heights, while keeping N levels above minimum requirements for functional mangrove leaves. In addition, the variation in sediment nitrogen concentration could have been partially affected by the variation in sediment bulk density, which ranged from 0.7 to 1.2 g cm −3 across our study sites (Garcias-Bonet et al, 2019). Bulk density has been shown to negatively correlate with soil nitrogen in coastal biogenic habitats (Fourqurean et al, 2012), although we did not find a correlation between bulk density and the concentration of N in the sediment or the mangrove leaves (linear regression; p = 0.122 and 0.874, respectively).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…N limitation, thus, is reflected in low mangrove canopy heights, while keeping N levels above minimum requirements for functional mangrove leaves. In addition, the variation in sediment nitrogen concentration could have been partially affected by the variation in sediment bulk density, which ranged from 0.7 to 1.2 g cm −3 across our study sites (Garcias-Bonet et al, 2019). Bulk density has been shown to negatively correlate with soil nitrogen in coastal biogenic habitats (Fourqurean et al, 2012), although we did not find a correlation between bulk density and the concentration of N in the sediment or the mangrove leaves (linear regression; p = 0.122 and 0.874, respectively).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, these two nutrients (P and Fe) are likely to be less available in seagrass compared to mangrove sediments in the Red Sea. In addition, sediments on the fringing mangroves in the Red Sea are more depleted in N relative to organic carbon than seagrass sediments (Garcias-Bonet et al, 2019), providing further evidence for inorganic N to be a limiting source for mangroves in the basin. Nevertheless, the mean Fe concentration in the Red Sea mangrove sediment was 0.58 ± 0.85%, which is much lower than the mean for marine sediment (4.1% DW; Bowen, 1979), and within the lower end of the global range for mangrove sediments (0.14-14.6% DW; Billah et al, 2014), highlighting the overall extremely oligotrophic conditions for mangroves in the Red Sea.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our chosen study sites were located in an enclosed lagoon with a high abundance of mangrove forests, leading to the conclusion that mangroves might be a major source of organic matter for our study sites. However, a recent study applying stable isotope mixing models found the major contributors to the organic matter in seagrass sediments in the Red Sea to be seagrass leaves and macroalgae blades, with contributions of 43 % and 37 %, respectively (Garcias-Bonet et al, 2019a).…”
Section: Effect Of Warmingmentioning
confidence: 99%